2018
DOI: 10.22146/ijc.21181
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Based Colorimetric Sensor for Anions: Experimental and TD-DFT Study

Abstract: The interactions between sensor chalcone of 3-(4-hydroxy-3-methoxyphenyl)-1-phenyl-2-propen-1- ABSTRAK Interaksi antara sensor chalcone dari 3-(4-hidroksi-3-metoksifenil)-1-fenil-2-propen-1-on (1) dan anion (F -,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It is considered that there are different conditions between experimental results and theoretical calculations. 129…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that there are different conditions between experimental results and theoretical calculations. 129…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that there are different conditions between experimental results and theoretical calculations. 129 The value of l max in the first excited state of the NH 2 -Cdots decreases (blue shift) after interacting with H 2 O 2 . The probability of absorption or emission of electromagnetic radiation in the transition between energy levels is represented by the oscillator strength ( f ).…”
Section: Excitation Characteristicsmentioning
confidence: 96%
“…One of the previous strategies adopted for the design of amine sensors is based on the use of coumarin-chalcone derivatives, which interact with anion through hydrogen bonding. In this paper we would like to report that compound of 3-(3-(3-Methoxy-4-hydroxybenzene)-prop-2-enoyl)-2H-2-chromenone (2), a coumarin-chalcone derivative, is a promising candidate for colorimetric chemosensor for amines because it has hydroxyl chalcone group as a binding site to form delocalization electron [9].…”
Section: Introductionmentioning
confidence: 99%
“…To model a defective system, a theoretical approach based on the density functional theory (DFT) is frequently conducted since DFT can successfully reproduce the experimental results [10][11][12][13]. In the previous theoretical studies, it was shown that borondoped diamond produces the blue-colored diamond, and nitrogen-doped diamond yields to the yellow one [1].…”
Section: Introductionmentioning
confidence: 99%